The effect of electrically pre-stressing of high DC electric field on performance of SDBD thruster in near space. (March 2023) - Liwei, Zhou; Liqiu, Wei; Zhou, Yang; Jingjing, Li; Desheng, Zhou; Hong, Li; Jingfeng, Tang; Yongjie, Ding
Abstract: The space charge on the surface of solid dielectric has great influence on the surface dielectric barrier discharge (SDBD). In this paper, the surface space charge of SDBD is effectively regulated by the effect of electrically pre-stressing of high DC electric field to improve the dynamic performance of ion wind thruster. The conduction current, surface charges, thrust and thrust-to-power ratio are measured respectively for the ion wind thruster with and without the effect of electrically pre-stressing. The experimental results show that compared with the ion wind thruster without the effect of electrically pre-stressing, the instantaneous polarization current of the SDBD ion wind thruster with the effect of electrically pre-stressing is reduced by 42.7%, and the attenuation constant of the relaxation polarization current is reduced by about 28.8%, which effectively reduces the relaxation polarization loss of the thruster under the alternating electric field. In addition, the discharge time of anode and cathode increases respectively by about 20.0% and 43.3%, and the variation of surface space charge increases by about 50.6% in one voltage cycle. The saturation thrust of the thruster is increased from 1070 μN/m to 1660 μN/m by about 55.1%. The maximum thrust-to-power ratio of the thruster is increased from 993 μN/kW to 2125 μN/kW by about 114.0%. Highlights: Initial instantaneous value of the response current of the PVDF under the pre-electric stress is reduced by about 42.7%, and the attenuation constant of the relaxation polarization current is reduced by about 28.8%, compared with the PVDF without the pre-electric stress. Comparing with the SDBD thruster without the pre-electric stress, the anode discharge time increases by about 20.0%, the cathode discharge time increases by 43.3%, and the surface space charge variation increases by about 50.6% during the discharge process. The saturation voltage of the SDBD ion-wind thruster increased from 4.8 kV to about 5.6 kV, and the saturation thrust increased from 1070 μN/m to about 1660 μN/m, with the increased amplitude of 16.7% and 55.1%, respectively. Due to the regulation effect of negative space charge on charged particles, the current passing through the SDBD thruster is relatively small. The thrust-power ratio increased by about 114.0%.